Психолого-педагогічні основи становлення перекладознавства та методик навчання перекладу - Коновалова, Вікторія Борисівна (НТУ "ХПІ", 2012)
У статті розглядаються психолого-педагогічні основи становлення перекладознавства та методик навчання перекладу. Робиться висновок про необхідність врахування принципу компаративізму, навчання фонових знань, розробки творчих вправ для навчання перекладу.

The article deals with psychological and pedagogical foundations of the formation of translation and translation teaching methods within the teaching of translation. The conclusion about the necessity of taking into account the background knowledge, developing creative activities for teaching translation have been made.
Psychological and pedagogic basis of translation and teaching methods formation
Keywords: компаративізм; знання фонові; вправи творчі; підготовка професійна; мова іноземна; комунікація